Utilisation of interactive media as health promotion in preventing and controlling blood sugar levels among type 2 diabetes mellitus patients: a systematic review - Ngurah Mahendra Dinatha (DiscoverSys Inc., 2019)
Background: The use of interactive media as a health promotion media has continued to develop in the past few decades. This technology is used to manage various acute and chronic diseases, one of which is diabetes mellitus. This systematic review aims to describe an intervention that utilises technology as a tool in the form of interactive media in conducting preventative health promotion and glucose control for type 2 diabetes.Methods: The databases used include ProQuest, PubMed, Science Direct and Google Scholar. The keywords used in article search are research, interactive media, type 2 diabetes, health promotion, telemedicine, web-based, obesity, diabetes exercise, walking, glucose control. Inclusion criteria are 1) articles published in 2014-2018 in English, 2) articles which the main content is about using interactive media for diabetes type 2 problems. Exclusion criteria are 1) literature that is not relevant to the purpose of writing, 2) researching the interactive media but not applied to the problem of type 2 diabetes, 3) duplication, and 4) published articles incomplete. Thus, there were 1442 articles and only 12 articles that were used in accordance with the inclusion and exclusion criteria.Results: This systematic review found that the effective results in the implementation of preventive health promotion and glucose control of type 2 diabetes by utilising technology particularly interactive media.Conclusion: The 12 articles used in this study revealed that the implementation of preventive health promotion by utilising technology particularly interactive media was sufficient to control the glucose levels of among patients with type 2 Diabetes Mellitus.